Low cost emergency water purification technologies / Chittaranjan Ray, Ravi Jain - Ray, Chittaranjan; Jain, Ravi (Integrated water security series, 2014)
[This book] provides the tips and techniques for supplying potable drinking water at low cost in the direst circumstances.